PLASMA MODIFICATION OF POLYVINYL ALCOHOL MICROFIBERS TO IMPROVE COHESION WITH CEMENT MATRIX - Jakub Ďureje; Zdeněk Prošek; Jan Trejbal; Pavel Tesárek (Acta Polytechnica CTU Proceedings, 2019)
The article describes plasma modifications of the surface of polyvinyl alcohol (PVA) microfibers using oxygen and hydrogen plasma in order to improve the properties of the composite material containing modified microfibers, cement and recyclate. Five different modification times 30, 60, 120, 240 and 480 seconds were applied. Changes on fiber surface were detected by SEM analysis, packed cell wettability measurement, and weight loss during modification. The selected durations of plasma treatment were chosen to produce test samples on which the modulus of elasticity was continuously measured and then bending and compression tests were performed. The measured values were compared with the reference samples. Oxygen modified fibers behavior is more hydrophilic compare with reference fibers, but hydrogen modified fibres behave more hydrophobic than reference fibers.